Antecedents and Consequences of Higher Education Financial Performance in Indonesia: Evidence from Private Higher Education Institutions in Indonesia - Suryo Pratolo; Arifin Hamsyah Mukti; Aristanti Widyaningsih (Universitas Pendidikan Indonesia, 2022)
Purpose: This study aims to examine the effect of accounting information systems and management accountability on financial and operational performance. Furthermore, it investigates the intervening role of financial performance on the effect of management accountability and operational performance.Design/methodology/approach: This research was conducted at private higher education institutions (HEIs) in Indonesia. Cluster sampling was used as a sampling technique, and 186 private HEIs were obtained. The survey method by distributing questionnaires was then carried out to collect research data. Moreover, data processing was performed utilizing Partial Least Squares (PLS).Findings: This study uncovered the key role of financial performance in direct or indirect influence on operational performance. In indirect influence, financial performance could be an intervention for management accountability and operational performance of private HEIs. In addition, the accounting information system had a positive effect on management accountability. Furthermore, management accountability had a positive effect on financial performance. Finally, management accountability had a positive effect on the operational performance of private HEIs.Originality: This study scrutinized the intervening role of financial performance on the relationship between management accountability and the operational performance of private HEIs. On the other hand, this research was carried out during the COVID-19 pandemic, the impact of which was also felt by private HEIs.Research limitation/implication: This research was only conducted based on data from private HEIs that became the research sample. Thus, the study results could not be generalized to all private HEIs.Practical implication: This study provides recommendations for the management of private HEIs to improve their operational performance through the application of management accounting in financial performance management, supported by an accounting information system.